Amino functionalized oligoimides telechelics - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Reddy, Krishna Mohan Srinivasulu; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Rajan, Chelanattukizhakkemadath Raman; Deokar, Sarika Babasaheb; Mulani, Khudbudin Baban; Ghorpade, Ravindra V.; Bhongale, Sunil Sitaram; et al. (2010)
This invention relates to a process for the preparation of amino functionalized oligoimide telechelics. More particularly it relates to a process for the preparation of soluble oligoimide prepolymers which can be used as matrix resins that can be rapidly cured to form stable polyimides with amino end functionalities. The amino functionalized oligoimide telechelics are suitable for conversion into three dimensional polymeric systems through condensation chemistry such as reaction with oligo epoxies (epoxy-imide resins), polyacids (polyamide imides) and polyhalogenated compounds (poly amine - imides) to form crosslinked structures having enhanced thermal stability and mechanical strength. The polymers prepared by the process of this invention can be used as materials in advanced composites having high temperature stability.

Amino functionalized oligo polyimides with enhanced storage stability - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Mohan, Srinivasulu Reddy Krishna; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Rajan, Chelanattukizhakkemadath Raman; Tayal, Rajiv Kumar; Shadbar, Qureshi Mohammed; Chavan, Nayaku; Deokar, Sarika Babasaheb; et al. (WO2012090055A1, 2012)
The invention relates to an improved process for the preparation of amino functionalized oligomeric monomeric reactant type polyimides having higher stability. More particularly it relates to a process for the preparation of soluble imide prepolymers, used as matrix resins that can be rapidly cured with multi-functional moieties such as diepoxy, dicarboxyl, anhydride, diisocyanates to form crosslinked structures having enhanced thermal stability and mechanical strength.

Ambient temperature photocopolymerization of tetrahydrofurfuryl methacrylate and isobornyl methacrylate: reactivity ratios and thermal studies - Rajdeo, K. S.; Ponrathnam, S.; Pardeshi, S.; Chavan, Nayaku; Bhongale, Sunil Sitaram; Harikrishna, Reghunathan (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2015)
Photocopolymerization of heterocyclic monomer namely, tetrahydrofurfuryl methacrylate with bulky bicyclic monomer, isobornyl methacrylate with different feed ratios was carried out in bulk with low concentration of an -hydroxyl ketone based photoinitiator. The ambient temperature photocopolymerization was carried out by using a UV-Visible lamp with fixed low intensity of 0.4mW cm(-2) for a period of 6min. The residual monomer remained in the polymerization process were determined by using gas chromatography. The reactivity ratio values for the two monomers were calculated from the copolymer composition data by using Fineman-Ross, Kelen-Tudos, Extended Kelen-Tudos and Mao-Huglin methods. Individually, as well as the average of all the methods revealed that the monomer reactivity ratios of tetrahydrofurfuryl methacrylate were higher than isobornyl methacrylate. The dyad sequence distribution and dyad sequence lengths were calculated using the Igarashi and Pyun method and the sequence length distribution for tetrahydrofurfuryl methacrylate was observed to be higher with an increase in its feed content. This supports the reactivity ratio studies that a higher monomer reactivity ratio value for tetrahydrofurfuryl methacrylate was observed as compared to its comonomer. The thermal studies showed that the glass transition temperatures of the copolymers increased with an increase in isobornyl methacrylate content.
Keywords: Copolymer; methacrylates; micro structure; photocopolymerization; reactivity ratios; thermal studies

Adsorptive removal of chromium(VI) using spherical resorcinol-formaldehyde beads prepared by inverse suspension polymerization - Mulani, Khudbudin; Patil, Vishwanath; Chavan, Nayaku; Donde, Kamini (Journal of Polymer Research, 2019)
The spherical cross-linked beaded polymers were prepared by condensation of resorcinol and formaldehyde in presence of tri-ethylamine by inverse suspension polymerization technique. The m-cresol, aniline, urea and thiourea were used as co-monomer and polyethylene glycol (PEG 400) was used as porogen. Paraffin oil was used as non-aqueous suspension agent. The polymeric spherical beads were prepared using various types of comonomers exhibiting range of particle size 77.62 to 158.84m at 90 degrees C and 300rpm for 4h. The resulting beads were analyzed by elemental analysis, particle size analysis and scanning electron microscope (SEM). The synthesized beads were used for the removal of Cr(VI) from aqueous solutions. A simple and sensitive solid phase extraction procedure was used for the determination of chromium at trace level by spectrophotometric method using 1,5-diphenylcarbazide reagent. The adsorption of Cr(VI) on the resorcinol-formaldehyde beads was monitored by energy-dispersive X-ray spectroscopy (EDX) analysis. The metal adsorption parameters such as contact time, pH, metal ion concentration and adsorbent dose were investigated. For Cr(VI), the maximum adsorption capacity was about 99% at pH2 for the resorcinol-formaldehyde beads obtained.
Keywords: adsorption kinetics; Beads; Chromium (VI); Formaldehyde; Inverse suspension; Resorcinol